Screening of native fungi for biodegradation of high-density polyethylene (HDPE) plastic in mangroves ecosystem - Ong, Ghim Hock; Liew, Li Ming; Wong, Kok Kee; Wong, Rui Rui; Jayanthi Barasarathi,; Loh, Khye Er; Tanee, Tawatchai (Penerbit Universiti Kebangsaan Malaysia, 2024)
Accumulation of high-density polyethylene (HDPE) plastic in the environment has become a global issue. A substantial amount of HDPE wastes ends up in the mangroves posing a significant menace to the ecology. Mitigation techniques using mycoremediation to treat the HDPE are gaining ground due to its sustainable approach. This study aims to screen and identify fungi isolated from a mangrove located in Kampung Kuala Lukut, Malaysia, that can degrade HDPE. From this study, eight fungi species were shown able to grow on HDPE as a sole carbon source in a Bushnell-Hass Broth culture. The identity of these isolates was confirmed using morphological observation and molecular identification using ITS1 and ITS4 primers. The ability of these eight fungi species to degrade plastic was assessed based on the percentage of weight loss of HDPE and the increment of fungal biomass. Results from this study show Aspergillus niger has the highest biomass increment, but Leptobacillium sp. shows the highest percentage of weight loss of HDPE. Thus, Leptobacillium sp. has the best potential to be developed as an efficient agent to degrade HDPE in an integrated plastic waste management system.